Brugada ECG pattern: a physiopathological prospective study based on clinical, electrophysiological, angiographic, and genetic findings - Duthoit, Guillaume; Fressart, Véronique; Hidden-Lucet, Françoise; Simon, Françoise; Kattygnarath, Darouna; Charron, Philippe; Himbert, Caroline; Aouate, Philip; Guicheney, Pascale; Lecarpentier, Yves; Frank, Robert; Hébert, Jean-Louis (Frontiers in Physiology, 2012)
See in the manuscript